The effect of Aloe Vera leaf gel in promoting wound healing and as antibacterial: Ali Aziz Al-Khayyat , Lubna Ahmed Kafi and Zena Munther A. Fahmi - Al-Khayyat, Ali Aziz (The Iraqi Journal of Veterinary Medicine, 2008)
This study was carried out to explore the effect of Aloe Vera leafgel in promoting wound healing and to investigate theantibacterial effect against some pathogenic bacteria in comparisonwith Nigella sativa oil. Standard dilutions of Aloe Vera leaf gel weremade from ten to one hundred percent and its antibacterial effecthad been examined in seeded agar method against Staphylococcusaureus and Pseudomonas aeruginosa both were previously identifiedby laboratory and biochemical methods, Nigella Sativa oil which isknown to be one of the important medicinal plant was used forcomparison . Statistical analysis showed a significant difference(P<0.05) between AVG and Nigella Sativa oil.The effect of Aloe Vera leaf gel against Staph .aureus was morepotent than against Pseudomonas aeruginosa. There was aproportional relation between different concentrations of AVGwith the values of inhibition zones diameters of the bacteria.Results showed that Aloe Vera was more potent than Nigella sativaagainst both bacteria.The Minimum Inhibitory Concentration (MIC) was sixtymg/ml and the Minimum Bactericidal Concentration (MBC) waseighty mg/ml for Staph .aureus.In order to investigate the effect of Aloe Vera gel on woundhealing, twenty-four local male rabbits were used. They weredivided into four equal groups and each animal was wounded inboth sides of the back region by making a one by two centimetersquare standard longitudinal incision with surgical scalpel. Thefirst group was a control group (wounded without treatment); thisgroup was employed to observe the normal wound healing. Thesecond group was treated with crude Aloe Vera leaf gel twice dailyfor 10 days. While the third group was wounded and infected withthe pathogenic bacteria Staphylococcus vaureus without treatment,in order to observe the natural body defense against pathogenicmicroorganisms. The last group was infected with the samebacteria but treated with crude Aloe Vera leaf gel to observe theantibacterial effect. The wounds in the left side in second andfourth group were left as self-control.